Femmes en guerres - Milquet, Sophie; Frédéric, Madeleine (Sextant, 2011)
War is usually considered a men's affair, where women would only play secondary roles. Although they are actresses and witnesses of history, they constantly see their experience devalued. Yet, given the scale of the conflicts of the nineteenth and twentieth centuries, the entire population was affected. Since women have mobilized in different ways, it seems important to promote a reading of the warlike phenomenon according to the prism of the genre. This book is part of this perspective. By collecting contributions from historians and writers, this book describes both the complexity of women's wartime experiences and their representations in literature.